Khaliduddin Strategi Komunikasi Ustadz dalam Meningkatkan Minat Belajar Alquran Santri di Dayah Darul Qur’an, Aceh, Indonesia - Khaliduddin Khaliduddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to determine the pattern of teachers’ communication to increase students’ interest in learning Quran; the efforts and obstacles faced by teachers in developing interest in learning the Quran, and to find out communication strategies to increase interest in learning Quran at Dayah Darul Quran Aceh. This research uses a descriptive analytical method with a qualitative approach. Place of research in Dayah Darul Quran Aceh Kuta Malaka. Sources of data collection through observation, interviews, and documentation. The results of this study are; 1) The pattern of communication teacher in increasing interest in teaching the Quran students' that most of the teachers use multi-way communication patterns and a small part uses two-way, 2) The efforts and obstacles faced by teachers in developing interest in learning study Quran self- are from five teachers explaining the efforts and obstacles what they face, including their efforts, namely providing direction, giving grades, giving awards, teachers always trying to learn and forming incentive classes, while the obstacles are a large number of students, lack of facilities and infrastructure, consistency and characteristic student, limited time. 3) The communication strategy carried out by the teacher in increasing interest in learning the Quran self-reliance, namely: repetition communication strategy, recruitment communication strategy, persuading communication strategy, guiding communication strategy, anticipatory communication strategy, and advice communication strategy.